Iron status in chronic kidney disease patients - Deori, Rumi; Bhuyan, Bedanta (International Journal of Research in Medical Sciences, 2017)
Background: In developing countries, chronic kidney disease (CKD) associated with anaemia is one of the major public health problems. With the progression of the disease, development of haematological abnormalities including iron deficiency increases. Renal anaemia may further increase the morbidity in these patients. Therefore, earlier detection and correction of anaemia may be helpful in preventing the progression of the diseases and its other adverse outcomes. Methods: The present study was designed to observe the iron status in diagnosed CKD patients (pre-dialysis). For this purpose, 50 adult diagnosed CKD subjects who were not on any haematinics were randomly selected from the Departments of Medicine and Nephrology in a tertiary care hospital in Assam, India. 50 age and sex matched healthy controls were also included. Haemoglobin concentration, serum iron, TIBC, transferrin saturation (TSAT) and serum creatinine were estimated by standard laboratory techniques. Statistical data were analyzed by using SPSS 21. Results: All the CKD subjects were anaemic with haemoglobin concentration below 11g/dl and 48% of them showed moderate degree of anaemia. Their serum creatinine level were >3mg/dl. The primary aetiologies of CKD were diabetes (44%) and hypertension (36%). Serum creatinine and total iron binding capacity (TIBC) were significantly (P <0.05) raised in CKD patients while serum iron was significantly lower in CKD subjects than in the control group. 26% of them had iron deficiency anaemia (TSAT <20%). Conclusions: Anaemia is one of the commonest and earliest manifestations in CKD patients. With serum creatinine >3 mg/dl, iron deficiency anaemia may be present.